Peran Teknologi dalam Reformasi Manajemen Pendidikan di Era Digital: Penelitian - Nordianus Wilfridus; Mentari Putri Wulan; Siti Zulaikha; Muh. Takdir (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
In the current day, attempts to improve the caliber and effectiveness of education have made digital transformation in educational management a top priority. This study examines how technology may be used to improve school management, describes the difficulties in putting it into practice, and looks at the potential it offers. Notwithstanding the enormous potential of technology to increase accessibility and customize education, obstacles including the digital divide, teacher competency gaps, and data privacy concerns continue to be major obstacles. Comprehensive approaches and regulations are therefore required, such as improving teacher training and digital literacy, fortifying technology infrastructure, and creating strict data protection guidelines.s.In order to build a creative and sustainable educational environment, it is suggested that the curriculum be modified to satisfy the demands of the twenty-first century and that cross-sector cooperation be encouraged. It is envisaged that by putting these strategies into practice, educational administration would be able to take advantage of technological advancements and successfully adjust to new difficulties, ultimately generating graduates who are equipped to handle future global issues.